Convenient synthesis of α-nitrooximes mediated by OXONE® - Napasawan Chumnanvej (2018)
© The Royal Society of Chemistry 2014. A novel OXONE® mediated direct difunctionalization of alkenes with NaNO2 in aqueous acetonitrile for the synthesis of α-nitrooximes was developed. The α-nitrooximes were readily prepared in moderate to high yields at room temperature under mild reaction conditions. The present protocol offers an easy and environmentally benign approach to access various α-nitrooximes derived from styrene derivatives.